Ensinando operações com grandezas físicas vetoriais no ensino médio através de uma unidade de ensino potencialmente significativa - Reis, Antonio Fernando (Universidade Federal de São Carlos, 2016)
The student learning obtained by memorizing the information transmitted by the teacher's narrative, for further reproduction in the assessment, shows that the classic way of teaching, leads to a mechanical and not significant learning. The proposal of this study is to report the development and application of a Potentially Meaningful Teaching Unit (PMTU) proposed by Moreira, based on the Theory of Meaningful Learning of Ausubel. The proposal was drawn up using the PMTU steps in which, at first the survey of students' prior knowledge about the theme vectors was performed through the collective construction of a conceptual map and then the content of vectors was presented more generally through problem- situations. From that on, each vector operation was addressed more specifically, aiming the progressive differentiation and the integrative reconciliation. The students' performance was accomplished through their active participation and motivation in solving the problem-situations, in class debates, in the construction of maps, in simulations and video productions, that is with the use of The Information and Communication New Technologies of (ICNT). The concepts that were discussed and presented in accordance with the steps of PMTU: scalar greatness, vector greatness, trigonometric relationships in the triangle rectangle, vector addition by the polygon, the parallelogram and components methods, scalar product (real number) by one vector, scalar product and vector product of two vectors. The use of this sequence showed the evidence of occurrence of significant learning by the students and, therefore, many of the difficulties of high school students understanding have been overcome, since they are now familiar with the determination of some physical greatness, through operations with vectors presented in analytical geometry.
Keywords: Unidade de ensino potencialmente significativa; Aprendizagem significativa; Operações com vetores; Novas tecnologias da informação e comunicação; Simulações computacionais; Potentially Meaningful Teaching Units (PMTU); Vector Operations; Computer simulations; Information and Communication New Technology (NTIC); Meaningful Learning; CIENCIAS EXATAS E DA TERRA